Decoupling Asia revisited - Cyn-young Park (Asian Development Bank (ADB), 2017)
The issue of decoupling is controversial. On the back of Asia's sustained high growth, the hypothesis that the region's business cycles would become increasingly independent of the global trend gained considerable attention. Asia was nonetheless hit hard by the global financial crisis and subsequent economic downturn. This paper focuses on the evolution and nature of macroeconomic interdependence between emerging East Asia and Group of 3 economies. First, the progress of regional economic integration has positively impacted the direction and magnitude of macroeconomic interdependence and growth spillovers both intraregionally and interregionally. Second, with the People's Republic of China (PRC) playing a central role in the regional production and trade network, its ongoing structural changes will likely influence Asia's economic integration both within and beyond the region through evolving trade and investment links. Finally, the paper employs a vector autoregression model to assess the impact of the United States (US) output, world trade, financial volatility, and the PRC output shocks on emerging East Asia. Findings suggest that the US economy remains an important source of external demand shock for the regional economy, although the impact of the PRC has increased sharply.
Keywords: F15; F36; F44; 330; business cycle; emerging Asia; financial integration; trade integration